Ibn Taymiyya's theodicy of perpetual optimism - Hoover, Jon (Islamic philosophy, theology, and science, 2007)
This comprehensive study of Muslim jurist Ibn Taymiyya's (d. 1328) theodicy of perpetual optimism exposits and analyses his writings on God's justice and wise purpose, divine determination and human agency, the problem of evil, and juristic method in theological doctrine.